The other face of OPEC : financial assistance to the Third World - Shihata, Ibrahim F. I. (London ; New York : Longman, 1982)
It identifies the OPEC member countries with the developing countries of the Third World. Statistically, it demonstrates that the aid provided by the OPEC countries, as a proportion of GNP, far exceeds aid provided by the West.
Includes bibliographical references.
occ 16/01/2019
Loans
Keywords: Economic assistance